The Social Care Practitioner as Assessor: 'People, Relationships and Professional Judgement'. (8th February 2018) - Symonds, Jon; Williams, Val; Miles, Caroline; Steel, Mike; Porter, Sue
Abstract: The research in this paper aimed to reflect on English social care practitioners' accounts of their assessment practices, and includes the point of view of disabled people who are assessed. The research took place just after the implementation of the 2014 Care Act, which focuses both on the 'well-being' principle and on outcomes defined by service users. We report here on a grounded theory analysis of thirty qualitative interviews with social care practitioners from four local authorities; the research was set up and conducted by and with disabled people, and included their insights at all stages, including analysis. We consider the positions taken by practitioners in relation to their clients and to the wider task of social work. We found that assessors saw themselves as allies of clients; almost a quarter of our participants had lived experience of disability themselves. However, they felt they had to exert professional judgement in deciding on the needs of those who lacked competence or who asked for too much. We suggest that assessment practices could benefit from a shift away from the individual towards societal barriers, and that some of the interactional problems in assessments may best be tackled via client-led training.